Methyl Bromide Measurements in the Taylor Dome M3C1 Ice Core - Saltzman, Eric; Aydin, Murat (IEDA: US Antarctic Program Data Center, 2014)
Abstract: The data set includes methyl bromide (CH3Br) measurements made on air extracted from 70 samples from the Taylor Dome M3C1 ice core. CH3Br was measured in air from the Taylor Dome ice core to reconstruct an atmospheric record for the Holocene (11-0 kyr B.P.) and part of the last glacial period (50-30 kyr B.P.).